Iatrogenic distal femur fractures after long proximal femur nailing: a three-case series with prevention and management strategies - Michael, Aibin B.; Goregoankar, Arvind B.; Wagh, Suyog; Chhatriwala, Burhannuddin Fakhruddin; Ramtake, Tushar Bharat (International Journal of Research in Orthopaedics, 2026)
Proximal femur nails (PFNs) are widely regarded as the gold standard for unstable intertrochanteric fractures due to their biomechanical strength and minimally invasive nature; however, complications such as iatrogenic distal femur fractures and anterior cortical perforation remain important concerns. This case series describes three such complications: a 56-year-old female who developed a postoperative distal femur fracture after long PFN fixation, managed with ORIF using a distal femur plate with distal locking screws, proximal unicortical screws, and cerclage augmentation; an 82-year-old female with a similar fracture pattern managed with distal femur plating and cerclage wire; and a 58-year-old male who sustained anterior cortical perforation of the nail and was treated conservatively with non-weight-bearing due to medical unfitness for revision surgery. These complications typically arise from femoral bow mismatch, nail design limitations, surgical technique factors, and patient-specific anatomy. Management options include distal femur plating with or without cerclage augmentation or conservative treatment in selected patients, while prevention hinges on careful preoperative planning, appropriate implant selection, and meticulous technique. Although uncommon, distal femur complications after long PFN require early identification and individualized management to prevent progression and ensure favorable outcomes.